Revisiting the Empty Tomb : The Early History of Easter - Smith, Daniel A. (Book collections on Project MUSE., 2010)
Daniel A. Smith Seeks to get behind the theological and apologetic concern to "prove" the resurrection and asks, where did the account of the early tomb come from, and what purpose did they originally serve? He shows that Paul is a valuable witness to the development of Easter traditions; that Q was already interested in connecting the disappearance of Jesus with his future role; that Mark was interested in the disappearance of Jesus, rather than in the empty tomb as such; and that both sources had interests different from the later Gospels.